PENINGKATAKAN HASIL BELAJAR SISWA KELAS IXA SMP NEGERI 2 TIAKUR PADA MATERI PERPANGKATAN DAN BENTUK AKAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN GUIDED DISCOVERY LEARNING - Okololy, Yohanis; Ratumanan, Tanwey G; Moma, La (Program Studi Pendidikan Matematika (Kampus Kab. Maluku Barat Daya) Universitas Pattimura, 2022)
This research is a classroom action research that aims to improve student learning outcomes on the material of powers and roots using the Guided Discovery Learning Model. The study was conducted on 29 students of Class IXA SMP Negeri 2 Tiakur. Initially planned to be carried out in 3 cycles, but in the second cycle classical completeness has been achieved, so it is limited to only two cycles. Data was collected using tests and observation results. Data analysis techniques used quantitative analysis and qualitative analysis. The criteria for completeness set out in this study are a minimum of 65% of students reaching the KKM, which is 69.The results of the analysis showed that in the first cycle, there were 9 students (31.03%) achieving the KKM with an average score of 68.78. Furthermore, reflection and revision of the learning devices were then applied to the second cycle. In the second cycle, 23 students (79.31%) achieved the KKM with an average score of 75.49. This means that there is an increase in classical completeness and the average value in the second cycle. Thus, it can be concluded that the cooperative learning model of guided discovery learning type can improve student learning outcomes in terms of rank and root form.